Israel's belligerence against Palestine: from the Balkans to Nusantara - Jazexhiu, Olsi (Gerakbudaya Enterprise, 2023)
After the fall of the Soviet Union, Israel and the United States of America have sought to advance Israel's agenda in the Muslim world and the ex-Soviet Space.